Fostering performance management by identifying key performance indicators for human capital in integrated reporting - Uzule, Kristine; Zarina, Vita; Shina, Inga (Business: Theory and Practice, 2024)
Human capital is widely recognized as a pivotal factor in driving economic development and ensuring the sustained success of organizations. In efforts to enhance transparency in reporting and elucidate the mechanisms through which organizational value is generated, businesses might turn to the integrated reporting framework, encompassing six key capital dimensions, including human capital. However, a notable gap exists in the standardization of essential performance indicators within this framework. Therefore, the primary aim of this research was to identify the fundamental concepts underlying key performance indicators specific to human capital within integrated reports. These identified indicators not only enhance the usability of integrated reporting frameworks but also resonate with the perspectives of economic theory on human resource management, delving into various facets of employee performance and well-being. Moreover, the study delved into how transformational and benevolent leadership styles can harmonize with both the integrated reporting framework and the suggested key performance indicators of human capital, offering insights into effective organizational management and sustainable value creation.